How a better understanding of nursing research roles may help to embed research into clinical structures. (22nd September 2022) - Smythe, Analisa; Carter, Vanda; Dube, Alisen; Cannaby, Ann-Marie
Abstract : Background: Despite efforts to build research capacity within nursing there are growing concerns about the lack of funding and support for nurses who wish to pursue a career in research. Aim: To explore how research capacity within the nursing profession can be increased. Discussion: The disparity in opportunity and support for such roles is a barrier to the growth of nursing research. This article examines the nomenclature that exists around nursing roles in research, including those of clinical research nurse, nurse researcher and clinical nurse academic, and the challenges associated with each of these roles. The authors reflect on their career paths, specifically the transition from clinical research nurse to nurse researcher. Conclusion: To grow research capacity within the nursing discipline, organisations must provide opportunities for research at all career stages, promote the fundamental role that research plays in the quality of patient care and highlight career pathways and roles in nursing research.